2001
DOI: 10.1021/cm0006446
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Cr(V) Peroxychromates M3CrO8·XH2O (M = Li, Na, Cs):  Model 3d1Systems Exhibiting Linear Chain Behavior and Antiferromagnetic Interactions

Abstract: A new class of Cr(V) peroxychromates, those containing waters of hydration (Li3CrO8·10H2O, Na3CrO8·14H2O and Cs3CrO8·3H2O), has been synthesized and characterized by single-crystal X-ray diffraction, magnetic susceptibility, specific heat, and EPR techniques. The Li salt crystallizes into the orthorhombic (Cmcm) group, whereas the Na and Cs salts exhibit the triclinic (P1̄) and monoclinic P2(1)/n space groups, respectively. Crystal structure analysis indicated the availability of low-dimensional spin-exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…These salts were found 54 to possess unusual properties since Cr atoms in the salts are in a Cr(V) state and the salts are expected to be ferroic. This was confirmed by the recent studies done by the Dalal group on M 3 CrO 8 (M = Na, K, Rb), 55 56 and M 3−x (NH 4 ) x CrO 8 (M = Na, K, Rb, Cs). 57 It was shown that the order−disorder transitions in the M 3−x (NH 4 ) x CrO 8 salts are strongly influenced by directions of hydrogen bonds.…”
Section: Introductionsupporting
confidence: 79%
“…These salts were found 54 to possess unusual properties since Cr atoms in the salts are in a Cr(V) state and the salts are expected to be ferroic. This was confirmed by the recent studies done by the Dalal group on M 3 CrO 8 (M = Na, K, Rb), 55 56 and M 3−x (NH 4 ) x CrO 8 (M = Na, K, Rb, Cs). 57 It was shown that the order−disorder transitions in the M 3−x (NH 4 ) x CrO 8 salts are strongly influenced by directions of hydrogen bonds.…”
Section: Introductionsupporting
confidence: 79%
“…Hydrated Cr(V) containing compounds such as Li 3 CrO 8 , Cs 3 -CrO 8 , and Na 3 CrO 8 also show g ⊥ > g || . 53 Similar assignments of Cr(V) in square pyramidal coordination on various supports with g ⊥ ∼ 1.97 and g || ∼ 1.94 have been reported by several authors. 15,41,44,45 For octahedral geometry, g ⊥ < g || , which does not agree with the experimental g values.…”
Section: X-ray Powder Diffractionsupporting
confidence: 83%
“…This is interesting because in many cases (Li 3 PO 4 , Li 2 AsO 4 ) the ground state is found to be d z 2 , as discussed by Greenblatt . Dalal has reported that in hydrated Cr(V) compounds such as Li 3 CrO 8 , Cs 3 CrO 8 , and Na 3 CrO 8 g ⊥ > g ∥ and the ground state is d x 2 - y 2 rather than d z 2 . We have also observed a similar situation in the present study.…”
Section: Resultsmentioning
confidence: 76%